Postawy studentów wybranych szkół wyższych Polski wschodniej wobec cukrzycy = Attitudes of students from east Poland's selected academies towards diabetes - Olga Dąbska; Katarzyna Pawlikowska-Łagód; Ewelina Firlej; Eliza Wołoszynek (Kazimierz Wielki University, 2016)
Dąbska Olga, Pawlikowska-Łagód Katarzyna, Firlej Ewelina, Wołoszynek Eliza. Postawy studentów wybranych szkół wyższych Polski wschodniej wobec cukrzycy = Attitudes of students from east Poland's selected academies towards diabetes. Journal of Education, Health and Sport. 2016;6(12):452-464. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.207993 http://ojs.ukw.edu.pl/index.php/johs/article/view/4074         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 16.12.2016.       Postawy studentów wybranych szkół wyższych Polski wschodniej wobec cukrzycy Attitudes of students from east Poland's selected academies towards diabetes   Olga Dąbska1, Katarzyna Pawlikowska-Łagód2, Ewelina Firlej3, Eliza Wołoszynek4   1Zakład Patologii i Rehabilitacji Mowy, Uniwersytet Medyczny w Lublinie 2Zakład Etyki i Filozofii Człowieka, Uniwersytet Medyczny w Lublinie 3Katedra Zdrowia Publicznego, Uniwersytet Medyczny w Lublinie 4Zakład Profilaktyki Chorób Przewodu Pokarmowego, Uniwersytet Jana Kochanowskiego w Kielcach   Słowa kluczowe: cukrzyca, stosunek do choroby, opinia publiczna   Streszczenie Wstęp. Czynnikami, które w znacznym stopniu kreują przekonania i zachowania zdrowotne ludności są posiadana wiedza oraz postawy społeczne, rozwijające się pod wpływem otaczającego środowiska. Przejawianie antyzdrowotnych zachowań, związanych w dużym stopniu z postępem cywilizacyjnym oraz niski poziom wiedzy diabetologicznej wśród młodych ludzi sprawia, iż stanowią oni grupę, która w sposób szczególny narażona jest na rozwój cukrzycy. Cel pracy. Poznanie postaw studentów wybranych szkół wyższych Polski wschodniej wobec cukrzycy. Materiał i metody. Badanie przeprowadzono na grupie 150 studentów. Narzędzie badawcze stanowiła ankieta Badanie Postaw Wobec Cukrzycy DAS3 Centrum Badań i Szkoleń na Temat Cukrzycy Uniwersytetu Michigan. Analizy materiału badawczego dokonano przy użyciu programu Microsoft Office Excel. Wyniki. Znaczna część badanych (74%) jest zdania, iż cukrzyca dotyka prawie każdej dziedziny życia diabetyka, a 89% sądzi, że choroba ta zmienia podejście do życia. Odnośnie roli chorego w procesie terapii 77% ankietowanych zgadza się, że osoby z cukrzycą są najważniejszymi członkami zespołu opieki diabetologicznej. Z kolei 89% studentów uważa, iż pracownicy medyczni powinni nabyć kompetencje w zakresie sprawowania funkcji edukatora diabetologicznego. Wnioski. Postawy studentów w większości podkreślają istotę najbliższego otoczenia w walce z chorobą. Badani twierdzą, że wszystkie typy cukrzycy są wielce uciążliwe dla życia chorego. Ankietowani byli zgodni, co do konieczności doskonalenia umiejętności edukatorskich i komunikacyjnych przez personel medyczny.       Key words: diabetes, attitude towards medical condition, public opinion   Summary Introduction. Knowledge (or lack thereof) and social attitudes developing under the influence of the local environment are factors that extensively shape people's health convictions and attitudes. Evincing of health damaging attitudes as a result of industrial progress and low level of knowledge about diabetes among young people makes them the most susceptible to the development of diabetes. Goal of work. Getting to know the attitudes of students from east Poland's selected academies towards diabetes. Data and methods. The research was conducted on the group of 150 students. DAS3 attitudes towards diabetes survey from the Michigan Diabetes Research and Training University was the research tool. The analysis of the data was conducted with the use of Microsoft Office Excel. Results. Significant amount of the surveyed (74%) thinks that diabetes influences almost every area of one's life and 89% of the surveyed think that this disease changes one's attitude towards life. 77% of the surveyed agrees that people with diabetes are the most important members of the diabetic care crew. 89% of the surveyed states that medical workers should be educated about diabetes and should acquire appropriate skills that would be helpful in dealing with the disease. Conclusion. Students' attitudes emphasize the importance of the environment when dealing with the disease. The surveyed claim that all types of diabetes are very burdensome to the afflicted. Students agreed that medical personnel should further develop their educational and communicational skills.